2018
DOI: 10.1021/acsaem.7b00228
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Interconductivity and Intraconductivity of Graphene Nanoribbons for a Directly Deposited, High-Rate Silicon-Based Anode for Li-Ion Batteries

Abstract: Batteries for high-rate applications such as electric vehicles need to be efficient at mobilizing charges (both electrons and ions). To this end, choice of the conductive carbon in the electrode can make a significant difference in the performance of the electrode. In this work, graphene nanoribbons (GNRs) are explored as conductive pathways for a silicon-based anode. Water-based electrospinning is employed to directly deposit poly(vinyl alcohol) (PVA)−silicon−graphene nanoribbon composite fibers on a copper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The high capacity is obtained due to the enhanced activation of silicon due to the presence of GNR. [38] The initial columbic efficiency for both Si/Gr/GNR with and without pores is very similar, 74.25 and 74.5, respectively, giving another confirmation of similar composition leading to similar electrochemical reactions and inline with our CV results. The loss of initial columbic efficiency is due to several factors such as 1) formation of SEI layer on SiNp, 2) high surface area of graphene sheets leading to the irreversible reactions, and 3) electrochemical activity of polyimide.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The high capacity is obtained due to the enhanced activation of silicon due to the presence of GNR. [38] The initial columbic efficiency for both Si/Gr/GNR with and without pores is very similar, 74.25 and 74.5, respectively, giving another confirmation of similar composition leading to similar electrochemical reactions and inline with our CV results. The loss of initial columbic efficiency is due to several factors such as 1) formation of SEI layer on SiNp, 2) high surface area of graphene sheets leading to the irreversible reactions, and 3) electrochemical activity of polyimide.…”
Section: Resultssupporting
confidence: 81%
“…Third, the added graphene nanoribbon (GNR), which is obtained from chemically unzipping carbon nanotube (CNT), acts as a conductive pathway to ensure that the silicon inside the voids is electronically connected to the graphene sheets and offers a pathway for shorter transport of the lithium ions. [37,38] To prove our hypothesis of mitigation of silicon volume expansion via the creation of internal pores, we also carry out in situ volume expansion measurements of small pouch cells via a dilatometer and compare the resulting mitigation of volume expansion for Si/Gr/GNR anode with pores and that without pores, finding a reduction of almost 50% in the volume expansion. To the best our knowledge, the interplay of creation of pores and the resulting mitigation of volume expansion over a number of charge/discharge cycles via in situ measurement have never been quantitatively probed before.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have already demonstrated that the Si–C composite is one of the best solutions for high-performance anodes in many cases. For instance, the C-coated Si materials, such as Si–C yolk–shell, Si particles in C fiber matrix, C-coated mesoporous Si, and graphene/Si composite anode exhibit much less volume expansion during lithiation and stable cycling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Along the theme of structural batteries and supercapacitors, recent studies have also made signicant progress designing electrode architectures that can be drop-in components to multifunctional or structural battery design and sustain mechanical stress independent of interface coupling challenges. [51][52][53][54][55] With this said, with a growing broad research interest in studying structural supercapacitors and batteries that require stable energy storage operation under mechanical loading, there surprisingly have been little to no studies studying interfaces and interface design in these systems.…”
Section: Introductionmentioning
confidence: 99%